IMPLEMENTASI MODEL PANTAU BERBANTU MEDIA PAPAN PIKTOGRAM DALAM MENGEMBANGKAN KEMAMPUAN PENYAJIAN DAN INTERPRETASI DATA PADA SISWA KELAS IV SEKOLAH DASAR - Tri Pamungkas, Mukti; Henny Dewi Koeswanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Data presentation and interpretation skills are essential components of statistics learning that should be developed from the elementary school level. This study aimed to describe the implementation of the PANTAU Learning Model assisted by pictogram board media in developing fourth-grade elementary school students' data presentation and interpretation skills. This study employed a descriptive qualitative approach involving 24 fourth-grade students at SD Negeri Kutamendala 06. Data were collected through observations, interviews, documentation, and student response questionnaires, and were analyzed using the interactive analysis model of Miles, Huberman, and Saldana. The findings revealed that the PANTAU Learning Model was implemented through five instructional stages: Observe, Collect, Present, Analyze, and Review, which effectively developed students' data presentation and interpretation skills. Students also demonstrated highly positive responses toward the learning process, with an average response score of 84.8%. The findings indicate that the PANTAU Learning Model assisted by pictogram board media can be implemented to develop elementary school students' data presentation and interpretation skills.